Recreational and tourist destination research methods - Bozhuk, Tetiana (Human Geography Journal, 2016)
The methodological basis of the concept RTDe are the main provisions of the modern structural and socio-economic geography to study the spatial and temporal aspects of relations in the system "Man - Nature" and related sciences (knowladge about a tourizm, recreational geography, natural resources, etc.) that appeal to spatial heterogeneity of the studied phenomena. In accordance with the established scientific and methodological principles, fundamental circuit and algorithm design-geographical research foundations RTDe system applied research methods in accordance with the objectives of objects and levels of study.To study and synthesis of theoretical and methodological approaches to determining the conceptual and terminology used RTDe research methods and logical structure and system analysis (structural and geographic analysis); in identifying and clarifying the spatial patterns of differences in territorial organization used methods of space-time analysis; for comparative characteristics of individual properties RTDe and regional level – comparative method; to systematize information, determine the classification categories of types and subtypes RTDe – methods of systematization and classification; to study the history of RTDe, the origin of their individual components and varieties – historical-geographical method; in the present state of research, planning and organizational and functional structure of different types RTDe methods applied field research (conducted in 2006-2013 years.) poll (questionnaire), peer assessment, recording and evaluation of Christian sacred objects for the needs of tourism and recreation, mathematical logic and computer graphics, and other cartographic modeling. At all stages of the research methods used general scientific information analysis, synthesis, systematization, generalization and analogies, verification, comparison and others.